Información de las fases para la planificación de la rentabilidad empresarial - Ros García, Juan; Ros García, María Del Rosario (Revista General de Información y Documentación, 2004)
A study of specialized information as a key to achieving business profitability. The immediate communication of client needs and market fluctuations can lead to the achievement of considerable benefits with minimum difficulty, thereby creating an economic cycle of which intelligent businesses can take advantage and form growth sectors.
Keywords: Intelligent businesses; Knowledge; Juan Ros García; Marketing; Information; Profit value; Clients; María del Rosario Ros García; Market fluctuation; Economic cycle; Growth sectors; Companies; Colaboration; Segmentation